2019
DOI: 10.11648/j.jfns.20190703.11
|View full text |Cite
|
Sign up to set email alerts
|

Using Date Seed Powder Nanoparticles and Infusion as a Sustainable Source of Nutraceuticals

Abstract: Egypt is the world's largest date producing country. Different functional foods pertaining to date seeds were attempted before. Phenolic phytochemicals are not well absorbed in gastrointestinal tract, which results in lower bioactivity. Nanotechnology helps to resolve poor oral bioavailability. Aim was to evaluate the in-vivo anti-inflammatory properties of date seed powder (DSP) nanoparticles (NPs) and infusion in rats fed a high fat diet (HFD). Twenty five Wistar rats were distributed among five groups; I (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The re-establishment of biomarkers of hepatic and renal function; found herein, supports findings reported by Salama et al (2019) who found that DSPK intake reduces levels of glucose, T-cholesterol, triglycerides, and the main indicators of renal function in diabetic rats DSPK has been proved to act synergistically with insulin to reduce hyperglycemia and prevent secondary outcomes of diabetes mellitus such as cardiovascular events and anxiety (Bikri et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…The re-establishment of biomarkers of hepatic and renal function; found herein, supports findings reported by Salama et al (2019) who found that DSPK intake reduces levels of glucose, T-cholesterol, triglycerides, and the main indicators of renal function in diabetic rats DSPK has been proved to act synergistically with insulin to reduce hyperglycemia and prevent secondary outcomes of diabetes mellitus such as cardiovascular events and anxiety (Bikri et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…These positive surface charges of PLN were crucial in determining the electrostatic interactions and adhesion characteristics with the gastric mucosa. It was reported by Salama et al (2019) that the transport of nanoparticles that have positive charges through epithelial cellular membranes was greater than the molecules that have no or negative charges, hence, enhancing their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Orabi and Shawky (2014) 194 reported a significant increase in mean corpuscular hemoglobin concentration (MCHC), hemoglobin level, and mean corpuscular hemoglobin (MCH), with a simultaneous decrease in testicular malondialdehyde levels in male albino rats orally treated with 2 mL per kg per day of date seed extracts for 60 days. In another study, Amany Alsayed et al (2019) 195 evaluated the effects of 1 g per kg per day of date seed nanoparticles infused in Wistar rats as a nutraceutical. The authors confirmed that treatment with date seed extract significantly reduced total cholesterol levels, C-reactive protein, and serum amyloid-alpha in the experimental group compared to the control group.…”
Section: Bioactive Components Of Date Seed and Pomacementioning
confidence: 99%